KEARIFAN LOKAL DALAM NOVEL SEULUSOH KARYA D. KEMALAWAT - Wildan Wildan (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
px; "> <This study aims at identifying the presented local wisdom reflected through life experience of a socio-cultural system in “Seulusoh” a novel by D. Kemalawati. The method used in this study is qualitative analytic method by applying content analysis and in-depth interview. The result of the study indicates that the local wisdom enucleated inthe novel includes the celebration of holy days such as Ramadan fasting, meugang, and Eid Fitr; the value inheritance from old generation to younger generation, grandparents to grandchildren, parents/teachers to children; skills in making and serving traditionalfood such as ie bu peudah and timphan; and also belief and myths. Those local wisdom are implied as a means to preserve the traditional values, the ability in reading nature’s signs, to maintain the family pride and tradition